The Real Wages and Living Conditions of Construction Workers in Santiago de Chile During the Later Colonial Period, 1788-1808 - Navarrete-Montalvo, J; Llorca-Jana, M (Ediciones Doyma, S.L., 2015)
The main objective of this article is to determine the real salaries and living conditions of construction workers in Santiago de Chile towards the end of the colonial period (c. 1788-1808). To achieve this purpose, we have used the methodology proposed by Allen to calculate real salaries in terms of welfare ratios. Our main conclusions are: the real salaries of non-qualified workers remained above the subsistence levels throughout the entire period studied in this work, pointing to a lack of labour force in Santiago for this period (in spite of a population increase during the same period); there was also a significant proportion of qualified workers in the construction sector who earned 2-3 times more than non-qualified workers, giving rise to a notable heterogeneity in the mean income of workers in this sector and a greater difference than in other cities; despite being above the subsistence levels, the real salaries of non-qualified workers in Santiago appear to be among the lowest in the region, in contrast with previous conclusions in this respect. © 2013 Published by Elsevier España, S.L.U. on behalf of Asociación Española de Historia Económica.
Keywords: Real salaries; Living conditions; Chile